Temporal Distribution of Price Changes: Staggering in the Large and Synchronization in the Small - Emmanuel Dhyne; Jerzy Konieczny (National Bank of Belgium, 2007)
Temporal distribution of individual price changes is of crucial importance for business cycle theory and for the micro-foundations of price adjustment. While it is routinely assumed that price changes are staggered over time, both theory and evidence are ambiguous. We use a large Belgian data set to analyze whether price changes are staggered or synchronized. We find that the more aggregate the data, the closer the distribution to perfect staggering. This result holds for both aggregation across goods and across locations. Our results provide support for Bhaskar's (2002) model of synchronized adjustment within, and staggered adjustment across, industries.
Keywords: E31; L16; D21; L11; 330; staggering; synchronization; aggregation; price setting; Einzelhandelspreis; Preisrigidität; Preiswettbewerb; Anpassungskosten; Belgien